Accounting for failures to reform in the Arab world1. Issue 2 (7th March 2017) - Commander, Simon
Abstract: Arab regimes have struggled to reform effectively and, as a consequence, have continued to perform poorly in terms of output and employment growth. Some Arab autocracies have experimented with partial liberalization, yielding benefits mainly for connected parties or cronies. There has been a chronic inability to craft policies capable of commanding widespread support in the population. Instead, the main groups in the economy have coalesced around the preservation of rents at the cost of achieving wider benefits. The paper attributes this not only to a combination of lack of credibility as well as issues of time consistency, but also to the failure to develop and present a coherent case for reforms capable of conferring benefits on the wider population, rather than concentrated benefits for a few.